STUDENTS’ RESPONSES ON ENGLISH DEPARTMENT LECTURERS’ COMPETENCE - Hizriani, Nani; Ramadhanti, Fitri (LET: Linguistics, Literature and English Teaching Journal, 2015)
Lecturers have an important role in students academic achievement. There are a number of qualities and competences required by good lecturers. This research is conducted to find out students? responses and  their expectations on English department lecturers? competence . There are ninety students of English Department which are taken from the fourth, sixth and eighth semester students involved in this study. Questionnaire,  interview, and documentation are used to gather the data . The result showed that  students? responses on English Department lecturers? professional competence is in good catergory with mean score 4.1 and total percentage 82%. Meanwhile, students? responses on English Department lecturers? pedagogical competence is categorized as good with mean score 4.0 and total percentage 80%.  Most students expect that the lecturers come on time to the class. They also expect that the lecturers use interesting media in teaching and learning, select appropriate method and technique in teaching, and give more feedbacks to the students. They also hope their lectures provide much time for consultation.